PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENANGANAN TINGKAT KECEMASAN PASIEN YANG AKAN MENJALANI TINDAKAN EGD DI RUMAH SAKIT DR.BRATANATA JAMBI - Yunidar Yunidar; Dwi Yunita; Joko Pitoyo (Jurnal Akademika Baiturrahim Jambi, 2017)
Backgorund:Gastrointestinal endoscopy is an examination procedure gastrointestinal tract directly using fiberoptic scope that aims to perform therapeutic or diagnostic examination. Patients who undergo endoscopic procedures may experience anxiety as a result of lack of information about the procedure, side effects of the procedure and the results of the examination will be accepted. as many as 182 patients who underwent EGD action in the period January-September 2016. The purpose of this study to determine the effect of deep breathing relaxation techniques to handling the anxiety level of patients undergoing EGD action in Jambi dr.Bratanata Hospital.Method:Design The study was a Pre Experiment with One group Pre Test Post Test Design where measurement of anxiety level is done twice: before being given relaxation techniques breath in (pre-test) and after being given the relaxation techniques of breath in (post test) This study was conducted on 6-17 Feb, 2017 at the Hospital dr.Bratanata with new patient population that will take action EGD and total sample of 10 people. Then dialysis univariate and bivariate using T-Test test test dependent.Result:In this study can be concluded There is the influence of deep breathing relaxation technique to handling the anxiety levels of patients undergoing EGD action in Jambi dr.Bratanata Hospital. With the T-Test statistic test obtained (P-Value = 0.001 <0.05).It can be used as input and consideration for the hospital dr. Bratanata Jambi, that the importance of deep breathing relaxation techniques performed for each patient who will act examination and treatment, in order to minimize the anxiety that exist in every patient.